Conceptualization of academic plagiarism from the perception of different agents of Higher Education (Innovaciones Educativas, 2022)
This research focuses on academic plagiarism, considering it a topic of current concern in Higher Education. The goal was to identify and analyze how plagiarism is understood by students, the teaching staff, and the academic managers of the three public universities of the Autonomous Community of Galicia (Spain). For this, an interview script was used in nine focus groups and applied online through Microsoft Teams. Therefore, we gathered the opinion of different university agents: seventeen professors, thirteen academic representatives, and eight students. We also gathered information on the most well-known types of plagiarism and the quantity and modality of said fraudulent behaviors. Furthermore, data scrutinization was carried out with the qualitative analysisprogram Atlas.ti 8. As a main result, the concept of plagiarism and its manifestations are not understood in the same way by the different groups of participants. According to the results, the main conclusion is the need to reach a common language regarding the concept and to identify these practices to take preventive measures and fight against new forms of plagiarism, such as buying/selling homework.
Keywords: Higher level education; Ethic; Teaching academic staff; College student; Education administrator; academic fraud